Kritika modernizma pri Nikoli Šopu in Gregorju Strniši skozi prizmo perenialistične šole - Premk Bogataj, Eva (Slavia Centralis, 2020)
This article presents the theoretical basis of Nikola Šop’s ‘machine civilization’ and Gregor Strniša’s ‘logic of vending’, using the apparatus of the Traditionalist School (René Guénon, Ananda Coomaraswamy, Frithjof Schuon in Seyyed Hossein Nasr). Radical criticism of the paradigm is reflected in individualism, rationalism, empiricism, scepticism, naturalism, ignorance of metaphysical principles, contempt for traditional knowledge and human enslavement to one’s own senses, etc. It is consistent with the paradigm of modernism, understood by the Traditionalist School as a deviation of traditionalism, which, on the contrary, protects tradition and regards symbols as an important means of transmission of traditional knowledge and messages. The article presents excerpts from Strniša’s poetry, dramas Driada, Samorog and Ljudožerci, and Šop’s poetry and drama Tajanstvena prela. In addition to the criticism of modernism, we also present characteristics of traditionalism: the metaphysical transparency of phenomena and the transmutation of things.
Keywords: Modernism; Traditionalist School; Nikola Šop; Gregor Strniša; Seyyed Hossein Nasr